2021
DOI: 10.4103/apc.apc_133_21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on pediatric cardiac services in India

Abstract: Background : COVID-19 pandemic has disrupted pediatric cardiac services across the globe. Limited data are available on the impact of COVID.19 on pediatric cardiac care in India. Aims : The aims are to study the impact of COVID-19 pandemic on the care of children with heart disease in India in terms of number of outpatient visits, hospitalizations, catheter-based interventions, and cardiac surgeries. Settings and Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Some good quality multicentric Indian data are also published. [ 25 - 30 ] Almost all the editorials in the last few years were India-centric. We tried to address some of the pertinent Indian problems, including the impact of COVID-19 on Indian pediatric cardiology,[ 31 ] minimum requirements for pediatric cardiac interventions,[ 32 ] fetal cardiology in India,[ 33 ] interventional cardiology,[ 34 ] research and key publications from India,[ 35 ] and Indian pediatric cardiology conference.…”
Section: Annals Of Pediatric Cardiology: a New Outlookmentioning
confidence: 99%
“…Some good quality multicentric Indian data are also published. [ 25 - 30 ] Almost all the editorials in the last few years were India-centric. We tried to address some of the pertinent Indian problems, including the impact of COVID-19 on Indian pediatric cardiology,[ 31 ] minimum requirements for pediatric cardiac interventions,[ 32 ] fetal cardiology in India,[ 33 ] interventional cardiology,[ 34 ] research and key publications from India,[ 35 ] and Indian pediatric cardiology conference.…”
Section: Annals Of Pediatric Cardiology: a New Outlookmentioning
confidence: 99%
“…[ 25 31 ] During the COVID-19 pandemic, the Pediatric Cardiac Society of India organized and reported a few retrospective multicenter studies. [ 32 33 ] It is the time for us to plan futuristic RCTs.…”
Section: Pediatric Cardiology Randomized Controlled Trials – Opportun...mentioning
confidence: 99%
“…A large, multicentric, retrospective study by Choubey et al . [ 3 ] reported outpatient footfalls, admission statistics, and procedural numbers during the first wave from 24 pediatric cardiac centers across the country and compared it with the corresponding period in 2019. The study documented 68%–75% reductions in outpatient visits (from 54,213 to 13,878), hospitalizations, cardiac surgeries, and catheterization procedures.…”
Section: Managing Children With Heart Diseasementioning
confidence: 99%
“…On the positive side, emergency procedures including arterial switch surgery, total anomalous venous connection repair, and balloon atrial septostomy showed the least decline during this period. Government-funded tertiary care centers reported a greater reduction[ 3 9 ] for obvious reasons and took a long time to normalize services. Data are needed on how these missed opportunities affect the natural history of CHD.…”
Section: Managing Children With Heart Diseasementioning
confidence: 99%